Basic Tahsin Learning in Agricultural Environment in the Al-Qur'an Reading Improvement Program in Sidamulya Village, Bongas District, Indramayu Regency - Ahmad Khotibul Umam; Tion Bahrian (Aslim: Journal of Education and Islamic Studies, 2024)
The term 'tahsin' is often associated with the activity of reading the Qur'an. This term has found a place in the hearts of the community, especially those who realize the importance of carrying out the routine of reading the Qur'an with all its perfection. The purpose of this community service is to Basic Tahsin Learning in the Agricultural Environment in the Qur'an Reading Improvement Program in Sidamulya Village, Bongas District, Indramayu Regency. The method in this Community Service (PkM) is to use counseling and mentoring, intending to understand the problems experienced by children. Teaching and also direct practice, such as teachers first reading verses of the Qur'an then followed by students. The approach to this program uses a phenomenological approach, starting with observing and examining the target objects of the program implemented in Sidamulya Village. The results of this Community Service are that many children are enthusiastic about learning this tahsin. Because with this tahisn learning, children can better understand the makhrijul huruf and the science of tajwid in the Qur'an.